1999
DOI: 10.1095/biolreprod60.4.1036
|View full text |Cite
|
Sign up to set email alerts
|

Spermatid Translocation in the Rat Seminiferous Epithelium: Coupling Membrane Trafficking Machinery to a Junction Plaque1

Abstract: In this study, we demonstrate that specialized junction plaques that occur between Sertoli cells and spermatids in the rat testis support microtubule translocation in vitro. During spermatogenesis, Sertoli cells are attached to spermatids by specialized adhesion junctions termed ectoplasmic specializations (ESs). These structures consist of regions of the plasma membrane adherent to the spermatid head, a submembrane layer of tightly packed actin filaments, and an attached cistern of endoplasmic reticulum. It h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Microtubules bind to ectoplasmic specializations attached to spermatids mechanically separated from the epithelium, and the binding is ATP dependent [31]. In motility assays, also using isolated spermatids with attached junctions, ectoplasmic specializations are capable of transporting microtubules [36]. Significantly, microtubules move both in the plus end direction and in the minus end direction across ectoplasmic specializations [9], a result consistent with the presence of at least two types of motor proteins on the structures and with the down and up directions of spermatid translocation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules bind to ectoplasmic specializations attached to spermatids mechanically separated from the epithelium, and the binding is ATP dependent [31]. In motility assays, also using isolated spermatids with attached junctions, ectoplasmic specializations are capable of transporting microtubules [36]. Significantly, microtubules move both in the plus end direction and in the minus end direction across ectoplasmic specializations [9], a result consistent with the presence of at least two types of motor proteins on the structures and with the down and up directions of spermatid translocation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies demonstrated that the intratesticular injection of taxol (an MT stabilizer) led to the retention of step 19 spermatids deep within Sertoli cells crypts, instead of being transported towards the tubule lumen (Russell et al 1989). Indeed, when mechanically isolated spermatids which retained their associated ES from the Sertoli cell were immobilized in a flow chamber, movement of fluorescently labelled MTs across the spermatid surface was observed in the presence of exogenous ATP (Beach & Vogl 1999). This illustrated that a force can be generated between ES-bearing spermatids and MTs that causes their movement in opposite directions.…”
Section: Crosstalk Between Different Cytoskeletal Elements During Spementioning
confidence: 99%
“…The parallel actin bundles of the ectoplasmic specialization junctional plaque are believed to function in part as a scaffold that supports and stabilizes an adhesive domain in the Sertoli cell plasma membrane [44,45]. They are also believed to act indirectly, via their connection to the cistern of endoplasmic reticulum, as a link to an underlying network of microtubules that may be responsible for changes in the depth of the ectoplasmic specialization-spermatid complex within the seminiferous epithelium [45,46]. Espin, the founding member of the espin family of actin-bundling proteins, was identified as a component of the parallel actin bundles in the ectoplasmic specialization junctional plaque …”
Section: Sertoli Cell Ectoplasmic Specializationsmentioning
confidence: 99%